Delayed payment of gratuity, pension, and post-retirement conditions - Ugo Chuks Okolie; Morrister Idibra (Universitas Airlangga, 2022)
The value of retirees' gratuity and pension will continue to grow as individuals reduce their reliance on family members to care for them in old age and accept the truth that they must care for themselves by saving for the future. Benefits for retirees have piqued the interest of policymakers and experts worldwide. Numerous articles have been written to assess Nigeria's previous pension system, the reasons for its failure, the shortcomings of the new pension system, and the influence of both the old and new pension systems on pensioners' wellbeing in Nigeria. Nonetheless, no study exists in Nigeria on the effect of delayed gratuity and pension payments on post-retirement situations. To close this divide, this study explores the effect of delayed gratuity and pension payments on retirees' willingness to keep their current position in Nigeria. This study analyzed secondary data obtained from published and unpublished books, journal articles, and online sources. It used content analysis to determine the relevance of the material collected to the study's scope. The study shows that delayed gratuity and pension payments contribute to pensioners' diminishing status, deteriorating health, and premature mortality shortly after retirement. The study consequently suggests that both public and private employers of labor do regular pre-retirement training for their employees to avoid the shame of seeing their retirees become penniless on the streets or succumb to an early death shortly after retirement.